Planar magnetron sputtering of Ti and TiO2 for polyethylene terephthalate track-etched membrane surface modification - Rossouw, Arnoux (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.